A pathology mimicking dental abscess: facial plexiform neurofibroma - Buket Ceylan Çalık Yılmaz; Alev Alaçam (Gazi University, 2019)
Introduction: Facial plexiform neurofibroma (FPN) is a rare tumor appearing on the face. It involves cranial or upper cervical nerves, and lesions show malign transformation at a low rate. It is especially seen in childhood. FPN is also a component of the diagnostic criteria for neurofibromatosis type 1 (NF1). NF1 is a common and multi-systemic syndrome. This case report aimed to present the oral and radiographic findings of FPN and NF1 diagnosed in a child patient. Case Report: A 9-year-old male patient diagnosed with NF1 applied to our clinic complaining from pain during eating in the left mandibular posterior region. Extraoral examination showed 'cafe-au-lait' blots and an asymptomatic swelling on the left cheek. Worm-bag-sensation was felt on palpation of the swelling. Intraoral examination showed swelling of the buccal mucosa, enlargement in the alveolar ridge and caries on all primary molar teeth. Periapical radiograph showed signs of infection and distal root resorption in tooth number 75. Panoramic radiograph revealed thinning of the mandibular ramus, dilatation of the mandibular foramen, deepening of the mandibular notch and prolongation of the coronoid process and condylar neck. The collected anamnesis together with the clinical and radiographical findings suggested that the swelling on the cheek was not due to a dental abscess; rather it was due to an FPN lesion. The patient's treatment was done and routine check-up appointments were arranged. Conclusion: During clinical evaluation, it should be kept in mind that FPN may be one of the reasons of facial asymmetries of non-odontogenic pathologies in pediatric dentistry.